Intranodal palisaded myofibroblastoma in the submandibular gland region: a case report - Zhang, Han; Wang, Min; Li, Liang; Shao, Shuo; Zheng, Ning (Frontiers in Oncology, 2024)
Intranodal palisaded myofibroblastoma (IPM) is a rare benign tumor of the lymph nodes, particularly in inguinal lymph nodes. IPM originating from the submandibular gland lymph nodes is rarely encountered in clinical practice. Herein, we report the case of a 31-year-old male patient with IPM of the submandibular gland region and describe in detail magnetic resonance imaging findings and pathology. Magnetic resonance imaging detected a heterogeneous lesion with a hypointense rim on T2-weighted imaging with specificity in the left submandibular gland region. This case report will contribute to the accumulation of experience in the diagnosis of this disease.